Pinyin to speech system: fostering Chinese speaking skill among non-native speakers of Chinese as a foreign language / Goh Ying Soon ... [et al.] - Soon, Goh Ying; Warris, Saiful Nizam; Mohd Adam, Aileen Farida; Sulaiman, Mohd Suhaimi (2013)
Non-native learners of Mandarin face problems of mastering the correct pronunciation of Mandarin which consequently affects their speaking skill. Chinese is a tonal language and there are approximately 2000 syllables in Chinese. The finite syllables can be used into forming infinite phrases and sentences for speaking to achieve communication purposes. Therefore, a pinyin to speech system can be actualized to assist students in strengthening their speaking skills. A web-based system that enunciates a typed pinyin text was developed. This is especially useful as students of UiTM are using pinyin to learn Chinese. Text to speech (TTS) can be used to improve the teaching of Chinese as a foreign language. This system can be very helpful as the Chinese courses UiTM are moving towards a blended learning mode. This system will not only help UiTM students in particular but also can be useful for all Chinese learners in general.